Attitude towards online classes among school and college going students during lockdown due to COVID-19 pandemic - Kumar, Saurav; Prakash, Shiv; Srivastava, Mona (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of the study was to assess the attitude of the school and college-going students towards online classes. Methods: An online cross-sectional study was conducted on 228 school and college-going students fulfilling inclusion and exclusion criteria selected through purposive sampling methods. A semi-structured online questionnaire consisting of a socio-demographic questionnaire and Attitude towards online classes (ATOC) questionnaire was prepared by the researcher using Google form. The link of the questionnaire was sent to all the selected respondents through WhatsApp messages and emails. The data was analyzed using the IBM SPSS version 20 software. The reliability of the attitude questionnaire was assessed using Cronbach’s alpha test. The association between categorical variables was assessed using Chi-square tests. The comparison between variables was assessed using the students independent t-test. Results: More than half of the respondents (51.32%) were found with a positive attitude towards online classes. There was a significant association found between attitude towards online classes and socio-demographic variables such as age (p<0.05), academic level (p<0.05), and family income (p<0.01). The respondents who attended online classes (p<0.05), have technical knowledge (p<0.01), and got supported by their parents in the study (p<0.05) were found significantly high positive attitudes towards online classes. There was a significant difference found in the attitude of the respondents who faced psychological disturbances such as a decline in attention-concentration (p<0.05), irritation-anger (p<0.01), and tension (p<0.05) due to online classes. Conclusions: Although, online classes are more beneficial for the students and teachers in their academic activities during the lockdown period due to the COVID-19 pandemic but it can’t take place of traditional face-to-face classes.